Prevalence of Anti-JC Virus (JCV) Antibodies in the Multiple Sclerosis (MS) Population in Cyprus: A Retrospective Study - Sakis Lambrianides; Christiana A. Demetriou; Andis Tillyris; Elena Kkolou; Eftychia Gaglia; Eleni Agkastinioti; Eleni Leonidou; Yiolanda-Panayiota Christou; Savvas S. Papacostas; Kleopas A. Kleopa; Theodoros Kyriakides; Marios Pantzaris (Neurology Research International)
Background and Purpose. Progressive multifocal leukoencephalopathy (PML) is a debilitating disease of the central nervous system caused by the ubiquitous polyomavirus JC (JCV) in immunocompromised hosts. In recent years, a new subpopulation of patients at risk for PML has emerged, due to the growing use of immunomodulatory or immunosuppressive therapies in autoimmune diseases such as multiple sclerosis (MS). The anti-JCV antibody index is used as a stratification tool in assessing the risk of developing PML. The objective of this study was to retrospectively describe the prevalence of anti-JCV antibodies in the MS population in Cyprus. Methods. We retrospectively collected the demographics of 214 MS patients in Cyprus who were screened for anti-JCV antibodies using the STRATIFY JCV™ assay between September 2011 and June 2018. Logistic regression analysis was used to examine the effect of demographic variables on seropositivity, and bivariate tests were used to assess the association between demographic characteristics and JCV AI index. Results. A total of 214 MS patients in Cyprus were tested. Overall anti-JCV antibody prevalence was 45.8% (95% confidence interval 37.2%–55.8%). We could not establish a significant association between seropositivity and increasing age or sex. In the subgroup analysis of natalizumab-treated patients, the annual seroconversion rate was 4.5%. Conclusions. Overall seroprevalence of anti-JCV antibodies in MS patients in Cyprus using the STRATIFY JCV assay was lower than the worldwide reported mean. Although previously reported, in our study, the anti-JCV antibody seropositivity was not associated with increasing age or sex.